Hubungan Self Compassion dengan Stres Family Caregiver Orang Dengan Skizofrenia (ODS) di Wilayah Kerja Puskesmas Mumbulsari Kabupaten Jember - Juwarti Juwarti; Emi Wuri Wuryaningsih; Muhammad Zulfatul A`la (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Schizophenia is a mental illness shows psycological disorder, violent behavior, and inability self care. This has created a burden for family caregiver, financially, social, and psychological. The purpose of this study to identified the relationship between self compassion and stress of schizophrenis family caregiver in Puskesmas (PHC) Mumbulsari Jember. The study used correlation study with the cross sectional approach. The sampling was counted 35 family caregiver using total sampling. The instrument used self compassion scale (α=0,89) and stres in family (α=0,977). The result showed that the average self compassion of family caregiver was 71.31(26-104). While the average stress of family caregiver was 18,74 (0-28). Bivariate analysis using pearson test showed that there was no correlation between self compassion and stress of schizophenia family caregiver in Puskesmas (PHC) Mumbulsari Jember. There was no correlation between stress of schizophenia family caregiver and gender, age, education level, profession, relationship with schizophenia patient, and long tending of family caregiver. This has showed that family caregiver covered stress and showed a positive self acceptance. Actually, family caregiver showed that noncompliance of patient recovery, many of them was not accompanying schizophenia patient to public health, and neglecting schizophenia patient. Counseling and health promotion should be enhanced psychological health of family caregiver in treating schizophrenia patient in community through public health care serving. Keywords: Schizophrenia, stress family caregiver, self compassion